Obtención de queso fresco con mezcla de leche de sacha inchi (Pukenetia Volubilis L.) y leche fresca - Fernandez Lopez, Ysabel (2014)
The objective of this research was to develop a cheese based on a mixture of cow's milk and sacha inchi's milk (Plukenetia volubilis L), ecotype Shanao. Three blends were selected: 60:40, 70:30 and 80:20% vtv (milk and sacha inchi's milk); all mixes were pasteurized and coagulated with calcium sulfate at three levels (0.1, 0.15 and 0.2 M) and citric acid at a concentration of 50 % w/v. Subsequently, coagulation time and curd yield were determined. And sensory characteristics as smell, taste and texture of the 9 samples were evaluated to determine the best technological alternative and develop the proximal, microbiological analysis and the textura profile test to characterize the final product. The results indicated that the cheese made with the mixture of 60:40% vtv, concentration of coagulant at three levels and citric acid at a concentration of 50% w/v, presented a weak curd. However, cheese with mixtures of 40 and 30% of sacha inchi's milk, have better nutritional value in terms of protein and fat (18.5%, 16.3% and 27.13%, 25.95%), compared to mixtures of 20% of sacha inchi's milk (14.30%, 24.50%). Reaching the values set by the National institute of Health, of the National Ministry of Health of Peru. The cheese made with a mixture of 80:20 % v/v in concentration of coagulant at 0.2 M, has a firm consistency. A similar behavior was observed in the 70:30 mixture at 0.15 M. However, based on the acceptability test, the technological option of 70:30 mixture presents organoleptic characteristics similar to a cheese based on cow's milk. Microbiologically, the product is apt for consumption. Sensorily, the cheese presented an acceptance of 67% compared to a commercial cheese based only on milk. The texture profile of the finished product was performed using a deformation percentage of 30 %, presenting values for hardness of 1.88 N , 0.08 of elasticity, 0.86 of cohesiveness, 0.36 N x s of adhesiveness, 1.62 N of gumminess and 0.13 N of masticability.